ANALISIS SEGMENTASI PASAR SAYURAN ORGANIK DI PULAU SAPARUA KABUPATEN MALUKU TENGAH - Valenszya Jozias; Natelda Rosaldiah Timisela; Marfin Lawalata (Universitas Sebelas Maret, 2020)
This research aims to determine the segmentation of the organic vegetable market. The research sample consisted of farmers and organic vegetable traders taken by a census of 13 respondents. While the consumer sample is taken by chance, the accidental sample is 40 respondents. The final cluster analysis results show that cluster 1, the Z-score is negative, that is, age and work, and in cluster 2, the Z-score is negative, namely education and income. This means that in cluster 1, consumers' age and occupation are still very minimal to determine choices in choosing organic vegetables for consumption. The same thing also happened in cluster 2, education and consumer income is still low to choose organic vegetables as consumer needs. The most considerable F value (56,156) is seen in the Z-score of education, with a significant number of 0,000, which means the significance is real. This means that educational factors significantly distinguish the characteristics of the two clusters. Or in other word, education in the two clusters is very different between cluster 1 and cluster 2.